2009
DOI: 10.1007/s10562-009-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Fast Esterification of Acetic Acid with Short Chain Alcohols in Microchannel Reactor

Abstract: Microchannel reactor was used for the fast synthesis of acetic acid esters, including methyl acetate, ethyl acetate, n-propyl acetate and n-butyl acetate. Effects of the inner diameter of microchannel reactors, dosage of catalyst, residence time, reaction temperature and molar ratio of alcohol to acetic acid on yields of esters were studied in the p-toluene sulfonic acid-catalyzed homogeneous esterification of acetic acid with alcohols. Yields of acetic acid ester reached 74.0, 70.1, 97.2 and 92.2% when methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The production of MeOAc from HOAc and MeOH has been kinetically mediated by homogeneous or heterogeneous catalysts, with more research being performed on the latter due to increased reusability, high selectivity, and less product contamination . The synthesis and kinetics via microwave, membrane, batch, and microchannel reactors have also been addressed . Most recent experimental investigations (from 2011) have reported free energy of activation for this process with values ranging from ∼7.7 to 15.1 kcal mol −1 in different reaction media/solvents at temperature up to 333 K. In addition to this parameter, some studies also provided heat of reaction (enthalpy, Δ H ) and entropy (Δ S ) of activation values within −1.0 and 0.1 kcal mol −1 for Δ H while 1.0 E −5 and 0.1 cal (mol K) −1 for the reaction entropy …”
Section: Introductionmentioning
confidence: 99%
“…The production of MeOAc from HOAc and MeOH has been kinetically mediated by homogeneous or heterogeneous catalysts, with more research being performed on the latter due to increased reusability, high selectivity, and less product contamination . The synthesis and kinetics via microwave, membrane, batch, and microchannel reactors have also been addressed . Most recent experimental investigations (from 2011) have reported free energy of activation for this process with values ranging from ∼7.7 to 15.1 kcal mol −1 in different reaction media/solvents at temperature up to 333 K. In addition to this parameter, some studies also provided heat of reaction (enthalpy, Δ H ) and entropy (Δ S ) of activation values within −1.0 and 0.1 kcal mol −1 for Δ H while 1.0 E −5 and 0.1 cal (mol K) −1 for the reaction entropy …”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are some reports on alkali-catalyzed transesterification for biodiesel production [27][28][29][30] and esterification of acids with alcohols [31,32] in microstructured reactors. The results indicated that the reaction time could be significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al. raised the yield of acetic acid esters to 70.1%, 74.0%, 92.2% and 97.2% in a microchannel reactor with the presence of ethanol, methanol, n‐butanol and n‐propanol, respectively, during the 14.7 min of residence . Aromatic nitration of acetyl guaiacol is highly exothermic and fast, and can be better controlled at high efficiency in the microreactor due to the acceleration of mixing and heat transfer.…”
Section: Introductionmentioning
confidence: 99%